Synthesis of Glycerol Monostearate by Esterification on H3PW12O40/MCM-41 Catalyst - Gu, Yi; Zhou, Lu; Niu, Lei; Hong, Mei; Xiao, Guomin (Asian Journal of Chemistry, 2014)
H3PW12O40/MCM-41 solid-acid catalyst with different phosphotungstic acid (H3PW12O40) loadings was prepared by impregnation method and used in the esterification of glycerol with stearic acid using N,N-dimethyl formamide as solvent. The catalyst was characterized by FT-IR spectroscopy, transmission electron microscopy and scanning electron microscopy. The effects of catalyst preparation and esterification parameters such as reaction time, stearic acid/glycerol ratio and reaction temperature on esterification were investigated simultaneously. The results showed that H3PW12O40/MCM-41 had the best catalytic properties when the H3PW12O40 loading was 30 % and the use of DMF had a significant improvement on the yield of monoglyceride. Under a reaction condition of 6 h, 433 K and glycerol/acid molar ratio 6:1, 91 % selectivity of glycerol monosteatate was achieved with a stearic acid conversion of 98 %.